DEVELOPMENT AND VALIDATION OF STABILITY INDICATING CHROMATOGRAPHIC METHOD FOR SIMULTANEOUS ESTIMATION OF SACUBITRIL AND VALSARTAN IN PHARMACEUTICAL DOSAGE FORM - Mishra, Shweta; Patel, C. J.; Patel, M. M. (International Journal of Applied Pharmaceutics, 2017)
Objective: This study aims to develop and validate a stability indicating HPLC method for simultaneous estimation of sacubitril and valsartan in pharmaceutical dosage form. Methods: Sacubitril and valsartan separation were achieved by LC-20 AT C18 (250 mm x 4.6 mm) column and buffer (potassium phosphate, pH 3.0): methanol (50:50) as mobile phase, at a flow rate of 1 ml/min (millilitre per minute). Detection was carried out at 224 nm (nanometer). The different HPLC experimental parameters were optimized and the method was validated according to the standard guideline. Forced degradation experiments were carried out by exposing sacubitril and valsartan standard and sample for thermal, photolytic, oxidative and acid-base hydrolytic stress conditions. Results: Retention time of sacubitril and valsartan were found to be 4.170 min (minute) and 6.530 min (minute) respectively. The method has been validated for linearity, accuracy, precision, LOD, and LOQ. Linearity observed for sacubitril is 12.25-36.75 Î¼g/ml (microgram per milliliter) and for valsartan is 12.75-38.25 Î¼g/ml (microgram per milliliter). The results showed that sacubitril and valsartan and the other degradation products were fully resolved and thus the proposed method is stability-indicating. Conclusion: The proposed HPLC method was found to be simple, specific, precise, accurate, rapid and economical for simultaneous estimation of valsartan and sacubitril in bulk and tablet dosage form. Thus the validated economical method was applied for forced degradation study of sacubitril and valsartan tablet.